The Role of Quality of Work Life on Job Stress and Turnover Intention Mediated by Job Satisfaction of Private Teachers in Tangerang District - Rani Pujiastri; Dimas Angga Negoro (Jurnal Manajemen Indonesia, 2023)
The purpose of the study was to explore the role of Quality of Work-life on Job Stress, Turnover intention mediated by job satisfaction. Referring to previous researchers' theory and empirical evidence, the authors collected the data by distributing questionnaires online to teachers teaching at private schools in the Tangerang district. Respondents were private teachers teaching at the elementary–high school level using purposive sampling methods. This research was a quantitative study with the Structural Equation Model (SEM) method. Some of the findings in this study were the first positive influence of Quality of Work Life, Job Satisfaction on Turnover intention. Second, the negative influence of Quality of Work Life, Job Satisfaction on turnover intention was insignificant, while there was no direct influence between Job Satisfaction, Job Stress, and Turnover intention. The managerial implication of research for Organizations is the increased quality of work life to improve the warm work environment. This will encourage positive change for teachers in particular and benefit the organization. Keywords— Job Satisfaction; Job Stress; Quality of Work Life; Turnover Intention